PERBEDAAN HASIL BELAJAR IPAS KELAS IV ANTARA MEDIA GAMBAR DENGAN MEDIA VIDEO DI SDN KUTABUMI IV KABUPATEN TANGERANG - Frizori Rendy Sukma; Sa’odah; Candra Puspita Rini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the differences in IPAS learning outcomes between students taught using image media and those taught using video media in Grade IV at SDN Kutabumi IV, Tangerang Regency. The research employed a quantitative method with a quasi-experimental approach using a nonequivalent control group design. The sample consisted of two classes, each receiving different treatments. Data were collected through pre-tests and post-tests. The results showed that students taught using video media achieved higher post-test scores compared to those taught using image media. This indicates that video media is more effective in improving students’ learning outcomes. Therefore, selecting appropriate instructional media is crucial to enhancing students’ understanding and motivation in IPAS learning.